Low-shrinkage copper slag-based cementing material and preparation method thereof

By preparing low -contraction of copper slag base gel materials, using solid waste such as copper residue, slag, and molor ash solve the problem of low use rate and environmental pollution of these wastes, and achieve efficient solid waste utilization and environmental protection effects.

CN119330679APending Publication Date: 2025-01-21ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411365947.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize solid waste such as copper slag, slag and fly ash, resulting in low utilization and environmental pollution.

Method used

By preparing low -contraction of copper slag base gel materials, copper, slag, and flour ash are used as the main raw materials, and an expansion agent, water reducing agent, water glass excitation agent and other auxiliary materials are added. Concubation material.

Benefits of technology

It achieves efficient utilization of copper slag, slag and fly ash, prepares cementitious materials with low shrinkage and high mechanical properties, solves environmental problems caused by solid waste storage, and improves the comprehensive utilization rate of industrial solid waste. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330679A_ABST
    Figure CN119330679A_ABST
Patent Text Reader

Abstract

The invention provides a low-shrinkage copper slag-based cementing material and a preparation method thereof, and relates to the field of solid waste utilization. The low-shrinkage copper slag-based cementing material is prepared from copper slag, slag, fly ash, standard sand, water, a water glass exciting agent, sodium hydroxide, a magnesium oxide expanding agent, a water reducing agent and magnesium-aluminum hydrotalcite. According to the invention, the defects in the prior art are overcome, the problem of environmental pollution caused by solid waste stockpiling can be solved by taking the copper slag and the fly ash as siliceous materials and the slag as a calcium-silicon raw material, and the method has important environmental protection significance for the society. The resource utilization of various solid wastes is realized, and the sustainable development of resources is promoted. The prepared cementing material has good physical and mechanical properties and durability, and the product performance meets the national standard requirement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid waste utilization, and in particular to a low-shrinkage copper slag-based gelling material and a preparation method thereof. Background Art

[0002] As a new type of building material, alkali-activated cementitious materials have obvious advantages such as excellent mechanical properties, good durability, energy saving and environmental protection. They are made of siliceous materials and calcium materials as the main raw materials, mixed with activators, stirred with water, and formed voids by chemical reactions, and then processed through static curing, demoulding and cutting. However, there are also problems such as poor volume stability and easy cracking. Copper slag has good potential for the preparation of alkali-activated cementitious materials. Therefore, studying the volume stability of alkali-activated copper slag materials has become the key to solving problems such as waste of copper slag resources.

[0003] Copper slag is a by-product of the copper smelting industry, and its production volume is relatively significant. Due to the close integration of mineral components in copper slag, it is difficult to achieve comprehensive utilization of it by traditional methods. At present, the recovery and utilization technology of copper slag is not yet mature, its utilization rate is low, and the recovery cost is relatively high. The main chemical components of copper slag are CaO, SiO2, Al2O3, Fe2O3, and MgO, and its mineral composition contains a large amount of amorphous glass such as gangue. At the same time, copper slag also has excellent characteristics such as firmness, wear resistance and stability. Therefore, after proper pretreatment, copper slag can partially replace traditional high-quality calcium silicon mineral raw materials as building materials.

[0004] Blast furnace slag is an industrial solid waste discharged during the iron-making process, and its main chemical components are CaO, SiO2, Al2O3, MgO, Fe2O3, V2O5, S, etc. The large-scale production and accumulation of blast furnace slag will not only cause environmental pollution and waste of resources, but also restrict the healthy development of the steel industry to a certain extent. Blast furnace slag reacts violently during the water quenching process, and some of the energy that is not completely released is stored in the form of chemical bonds, so it has high chemical activity. The alkaline activator can well activate the activity of blast furnace slag, promote the hydration reaction of blast furnace slag, and shorten the induction period.

[0005] Fly ash is fine solid particles captured from the flue gas generated in the coal combustion process. It mainly comes from the production and supply of electricity, heat and other industries using coal-fired facilities. The amount produced is huge, and the amount produced in recent years has been more than 600 million tons. The chemical composition of fly ash is mainly SiO2 and Al2O3, and other components are Fe2O3, CaO, MgO, K2O, Na2O, SO3 and unburned organic matter. Under certain conditions, it can react with water to form a cementitious substance similar to cementitious cement, and has a certain strength. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a low-shrinkage copper slag-based cementitious material and a preparation method thereof, which can process a large amount of environmentally harmful solid wastes such as copper slag, slag and fly ash, solve the technical problems related to the low comprehensive utilization rate and environmental pollution of copper slag, slag and fly ash, and realize the sustainable utilization of industrial solid wastes.

[0007] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0008] A low shrinkage copper slag-based cementitious material, which comprises a mixture and auxiliary materials, wherein the mixture comprises the following raw materials in parts by weight: 180-220 parts of copper slag, 120-180 parts of slag, 120-180 parts of fly ash, 1250-1450 parts of standard sand, and 180-220 parts of water; the weight percentage of each component in the auxiliary materials to the total amount of dry materials in the mixture except water is as follows: expansion agent accounts for 2%-4% of the weight of the dry materials, water reducer accounts for 0.5%-1.5% of the weight of the dry materials, water glass activator accounts for 10%-15% of the total amount of the dry materials, magnesium aluminum hydrotalcite accounts for 2.5%-3.5% of the weight of the dry materials, and sodium hydroxide accounts for 2%-3% of the weight of the dry materials.

[0009] Preferably, the copper slag has a particle size range of 3.06 μm-240.30 μm, a median particle size D50 of 44.14 μm, and a specific surface area of ​​1325-1420 m 2 / kg.

[0010] Preferably, the specific surface area of ​​the slag is 1015-1042m 2 / kg.

[0011] Preferably, the expansion agent is a magnesium oxide expansion agent.

[0012] Preferably, the water reducer is FK-A type polycarboxylate water reducer.

[0013] Preferably, the preparation method of the water glass activator comprises the following steps:

[0014] S1, dissolving flaky sodium hydroxide in warm water and letting it stand to prepare a sodium hydroxide solution for standby use;

[0015] S2. Use the above sodium hydroxide solution to add it dropwise into the water glass stock solution, adjust it to a modulus of 1.6 and a basicity of 6, stir it until it is completely dissolved, then let it stand and cool, to obtain a water glass activator.

[0016] Preferably, the temperature of the warm water dissolution in step S1 is 30-40° C., and the standing time is 24 hours.

[0017] The preparation method of the low shrinkage copper slag based gelling material comprises the following steps:

[0018] (1) adding water, copper slag, slag, fly ash, standard sand, expansion agent, water reducing agent and magnesium aluminum hydrotalcite into a stirring pot in sequence, and stirring at a low speed to obtain a mixture;

[0019] (2) Adding water glass activator into the mixture and continuing stirring, adjusting the high speed stirring after the stirring is completed to obtain a low shrinkage copper slag based gelling material.

[0020] Preferably, the low-speed stirring speed in step (1) is 140±5 r / min, and the stirring time is 10 s.

[0021] Preferably, in step (2), the rotation speed of continued stirring is 140±5 r / min, the stirring time is 140 s, and the rotation speed of high-speed stirring is 285±10 r / min, and the stirring time is 60 s.

[0022] The present invention provides a low shrinkage copper slag-based gelling material and a preparation method thereof, which has the following advantages over the prior art:

[0023] (1) The present invention uses solid wastes such as copper slag, slag, and fly ash as raw materials, and reasonably utilizes the copper slag, slag, and fly ash to prepare copper slag-based cementitious material test blocks. The copper slag-based cementitious material test blocks obtained by the present invention have low shrinkage and high mechanical properties, achieving the purpose of processing a large amount of copper slag, slag, and fly ash;

[0024] (2) The raw materials of the present invention use copper slag and fly ash as siliceous materials and slag as silicon-calcium material, which can solve the environmental problems caused by solid waste storage and realize the transformation of waste into treasure; the prepared copper slag-based cementitious material test block has good volume stability and mechanical properties, and the product performance can meet the national standard requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a graph of the compressive strength of the copper slag-based cementitious material obtained in Examples 1-3 of the present invention;

[0026] Figure 2 This is a graph of the compressive strength of the copper slag-based cementitious material obtained in Comparative Examples 1-2 of the present invention;

[0027] Figure 3 This is a drying shrinkage diagram of the copper slag-based cementitious material obtained in Examples 1-3 of the present invention;

[0028] Figure 4 This is a drying shrinkage diagram of the copper slag-based cementitious material obtained in Comparative Examples 1-2 of the present invention;

[0029] Figure 5 This is a SEM image of the copper slag-based cementitious material obtained in Example 2 of the present invention;

[0030] Figure 6This is a SEM image of the copper slag-based gelling material obtained in Comparative Example 1 of the present invention;

[0031] Figure 7 This is a SEM image of the copper slag-based cementitious material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The copper slag used in the following examples and comparative examples is high-temperature water-quenched slag, which is taken from the Tongling Nonferrous Metal Smelter in Anhui Province. The particle size of the copper slag ranges from 3.06 μm to 240.30 μm, with a particle size of 20 to 120 μm being the majority. The median particle size of the copper slag is D50 = 44.14 μm, and its specific surface area is 1325 to 1420 m 2 / kg, and the contents of the main components in the copper slag are shown in Table 1 below:

[0034] Table 1

[0035] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO CaO <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> content 24.01% 6.77% 2.61% 10.72% 41.24% 3.08%

[0036] The slag is taken from the Lingshou County Mineral Products Processing Plant, with a specific surface area of ​​1015-1042m 2 / kg, and the contents of the main components in the slag are shown in Table 2 below:

[0037] Table 2

[0038] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO MgO <![CDATA[Fe2O3]]> <![CDATA[Na2O]]> content 27.92% 15.66% 40.58% 9.83% 0.35% 0.59%

[0039] The fly ash was obtained from Gongyi Borun Refractory Material Co., Ltd., and the contents of the main components in the fly ash are shown in Table 3 below:

[0040] Table 3

[0041] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO CaO <![CDATA[Fe2O3]]> <![CDATA[K2O]]> content 55.78% 34.69% 0.25% 1.47% 3.56% 1.32%

[0042] The expansion agent is magnesium oxide expansion agent provided by Wuhan Sanyuan Special Building Materials Co., Ltd., and the content of each component in the expansion agent is shown in Table 4 below:

[0043] Table 4

[0044] Element <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO CaO <![CDATA[Fe2O3]]> content 8.17% 0.18% 83.96% 3.68% 1.05%

[0045] The water reducer was obtained from Shandong Laiyang Hongxiang Building Admixture Factory, and its main component was FK-A type polycarboxylate water reducer;

[0046] Magnesium aluminum hydrotalcite was analytically pure and provided by Hefei Tissue Culture Biotechnology Co., Ltd.;

[0047] Water glass, sourced from Jiashan Yourui Refractory Material Co., Ltd.;

[0048] Sodium hydroxide was of analytical grade and was obtained from Jixiang Chemical Co., Ltd.

[0049] The preparation of water glass activator is as follows:

[0050] The sodium hydroxide solution is prepared by dissolving sodium hydroxide in warm water at 30-40°C and standing for 24 hours after dissolution; the sodium hydroxide solution is slowly dripped into the water glass stock solution to prepare a water glass activator with a modulus of 1.6 and an alkalinity of 6, and the mixture is stirred until completely dissolved, and then the stirring is stopped, and the mixed solution is stood for 3 hours and then cooled to obtain the final water glass activator.

[0051] Embodiment 1:

[0052] Preparation of low shrinkage copper slag based cementitious material:

[0053] (1) Prepare the materials according to the following weight parts:

[0054] 180 parts of copper slag, 120 parts of slag, 120 parts of fly ash, 1350 parts of standard sand, 200 parts of water, 36 parts of magnesium oxide expansion agent, 9 parts of water reducer, 180 parts of water glass activator, 45 parts of magnesium aluminum hydrotalcite, and 36 parts of sodium hydroxide;

[0055] (2) Add water, copper slag, slag, fly ash, standard sand, magnesium oxide expansion agent, water reducer and magnesium aluminum hydrotalcite into a stirring pot in sequence, stir for 10 seconds at a low speed of 140±5r / min, gradually add water glass activator and continue stirring for 140 seconds. After the stirring is completed, stir again at a high speed of 285±10r / min for 60 seconds to produce the required gelled slurry.

[0056] Embodiment 2:

[0057] Preparation of low shrinkage copper slag based cementitious material:

[0058] (1) Prepare the materials according to the following weight parts:

[0059] 220 parts of copper slag, 130 parts of slag, 130 parts of fly ash, 1350 parts of standard sand, 200 parts of water, 30 parts of magnesium oxide expansion agent, 12 parts of water reducer, 50 parts of magnesium aluminum hydrotalcite, 180 parts of water glass activator, and 30 parts of sodium hydroxide;

[0060] (2) Add water, copper slag, slag, fly ash, standard sand, magnesium oxide expansion agent, water reducer and magnesium aluminum hydrotalcite into a stirring pot in sequence, stir for 10 seconds at a low speed of 140±5r / min, gradually add water glass activator and continue stirring for 140 seconds. After the stirring is completed, stir again at a high speed of 285±10r / min for 60 seconds to produce the required gelled slurry.

[0061] Embodiment 3:

[0062] Preparation of low shrinkage copper slag based cementitious material:

[0063] (1) Prepare the materials according to the following weight parts:

[0064] 215 parts of copper slag, 150 parts of slag, 120 parts of fly ash, 1350 parts of standard sand, 200 parts of water, 38 parts of magnesium oxide expansion agent, 6 parts of water reducer, 40 parts of magnesium aluminum hydrotalcite, 180 parts of water glass activator, and 30 parts of sodium hydroxide;

[0065] (2) Add water, copper slag, slag, fly ash, standard sand, magnesium oxide expansion agent, water reducer and magnesium aluminum hydrotalcite into a stirring pot in sequence, stir for 10 seconds at a low speed of 140±5r / min, gradually add water glass activator and continue stirring for 140 seconds. After the stirring is completed, stir again at a high speed of 285±10r / min for 60 seconds to produce the required gelled slurry.

[0066] Comparative Example 1:

[0067] Preparation of slag cementitious materials:

[0068] (1) Prepare the materials according to the following weight parts:

[0069] 200 parts of copper slag, 350 parts of slag, 120 parts of fly ash, 1350 parts of standard sand, 200 parts of water, 180 parts of water glass activator, and 30 parts of sodium hydroxide;

[0070] (2) Weigh copper slag, slag, fly ash, standard sand and water, add them into a stirring pot in sequence, stir at a low speed of 140±5r / min for 10s, gradually add water glass activator and continue stirring for 140s. After the stirring is completed, stir again at a high speed of 285±10r / min for 60s to produce the required gelled slurry.

[0071] Comparative Example 2:

[0072] Preparation of slag cementitious materials:

[0073] (1) Prepare the materials according to the following weight parts:

[0074] 210 parts of copper slag, 150 parts of slag, 100 parts of fly ash, 1350 parts of standard sand, 200 parts of water, 180 parts of water glass activator, and 30 parts of sodium hydroxide.

[0075] (2) Weigh copper slag, slag, fly ash, standard sand and water, add them into a stirring pot in sequence, stir at a low speed of 140±5r / min for 10s, gradually add water glass activator and continue stirring for 140s. After the stirring is completed, stir again at a high speed of 285±10r / min for 60s to produce the required gelled slurry.

[0076] Detection:

[0077] The mechanical property test of the copper slag-based cementitious material test block complies with GB / T17671-1999 "Test Method for Cement Mortar Strength", and the drying shrinkage test complies with the provisions of "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009). The cementitious slurries prepared in the above Examples 1-3 and Comparative Examples 1-2 were respectively set and tested, wherein the sample setting method is:

[0078] After each group has completed the preparation of the cementitious slurry, they will immediately start molding: fix the test mold on the compaction table, and then use a spoon to load the cementitious slurry into the test mold twice; when loading for the first time, the height of the test mold groove is 1 / 3 of its total height, and then use a scraper to smooth the mortar back and forth along each mold groove once, and compact it for 60 seconds;

[0079] Fill the test mold completely for the second time, smooth the cement paste with a scraper again, and vibrate it for another 60 seconds. Then, remove the mold sleeve and take down the test mold;

[0080] Transfer it to a standard curing box (curing conditions are temperature 20℃±1℃, relative humidity ≥90%). After curing for 24 hours, take out the test mold and demould it, then put the test piece back into the standard curing box and continue curing to the specified age.

[0081] The compressive strength and drying shrinkage of each group of material test blocks at different times are shown in Figure 1 , Figure 2 , Figure 3 , Figure 4 , and the 28d compressive strength and 180d drying shrinkage are shown in Table 5 below:

[0082] Table 5

[0083] Group 28d compressive strength 180d drying shrinkage Example 1 68.3MPa 0.0925% Example 2 72.8MPa 0.0837% Example 3 62.8MPa 0.1237% Comparative Example 1 60.8MPa 0.1673% Comparative Example 2 58.6MPa 0.1845%

[0084] It can be seen from the above table that the materials prepared in Examples 1-3 have better compressive strength at 28 days than Comparative Examples 1-2, and the 180d drying shrinkage rate of the materials in Examples 1-3 is significantly lower than that in Comparative Examples 1-2.

[0085] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A low shrinkage copper slag based cementitious material, characterized in that: The low shrinkage copper slag-based cementitious material is composed of a mixture and auxiliary materials, wherein the mixture is composed of the following raw materials in parts by weight: 180-220 parts of copper slag, 120-180 parts of slag, 120-180 parts of fly ash, 1250-1450 parts of standard sand, and 180-220 parts of water; The weight percentage of each component in the auxiliary material to the total dry material in the mixture except water is as follows: the expansion agent accounts for 2%-4% of the dry material weight, the water reducer accounts for 0.5%-1.5% of the dry material weight, the water glass activator accounts for 10%-15% of the total dry material weight, the magnesium aluminum hydrotalcite accounts for 2.5%-3.5% of the dry material weight, and the sodium hydroxide accounts for 2%-3% of the dry material weight.

2. The low shrinkage copper slag-based cementitious material according to claim 1, characterized in that: The copper slag has a particle size range of 3.06 μm-240.30 μm, a median particle size D50 of 44.14 μm, and a specific surface area of ​​1325-1420 m 2 / kg.

3. The low shrinkage copper slag-based cementitious material according to claim 1, characterized in that: The specific surface area of ​​the slag is 1015-1042m 2 / kg.

4. The low shrinkage copper slag-based cementitious material according to claim 1, characterized in that: The expansion agent is a magnesium oxide expansion agent.

5. The low shrinkage copper slag-based cementitious material according to claim 1, characterized in that: The water reducer is FK-A type polycarboxylate water reducer.

6. The low shrinkage copper slag-based cementitious material according to claim 1, characterized in that: The preparation method of the water glass activator comprises the following steps: S1, dissolving flaky sodium hydroxide in warm water and letting it stand to prepare a sodium hydroxide solution for standby use; S2. Use the above sodium hydroxide solution to add it dropwise into the water glass stock solution, adjust it to a modulus of 1.6 and a basicity of 6, stir it until it is completely dissolved, then let it stand and cool, to obtain a water glass activator.

7. The low shrinkage copper slag-based cementitious material according to claim 6, characterized in that: In the step S1, the temperature of the warm water dissolution is 30-40° C., and the standing time is 24 hours.

8. A method for preparing a low shrinkage copper slag-based cementitious material as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) adding water, copper slag, slag, fly ash, standard sand, expansion agent, water reducing agent and magnesium aluminum hydrotalcite into a stirring pot in sequence, and stirring at a low speed to obtain a mixture; (2) Adding water glass activator into the mixture and continuing stirring, adjusting the high speed stirring after the stirring is completed to obtain a low shrinkage copper slag based gelling material.

9. The preparation method according to claim 1, characterized in that: The low-speed stirring speed in step (1) is 140±5 r / min, and the stirring time is 10 s.

10. The preparation method according to claim 1, characterized in that: In the step (2), the speed of continued stirring is 140±5 r / min, the stirring time is 140 s, the speed of high-speed stirring is 285±10 r / min, and the stirring time is 60 s.

Citation Information

Cited By

  • Ultra-low carbon clinker-free cement and preparation method and application thereof

    CN121651788A

  • An ultra-low-carbon clinker-free cement, a preparation method and application thereof

    CN121651788B